Life Cycle Strategies of the Centric Diatoms in a Shallow Embayment Revealed by the Plankton Emergence Trap/Chamber (PET Chamber) Experiments - Ishii, Ken-Ichiro; Matsuoka, Kazumi; Imai, Ichiro; Ishikawa, Akira (Frontiers in Marine Science, 2022)
In situ emergence of the centric diatoms from the surface sediment, along with the occurrence of the vegetative cells in the water column, were monitored monthly in a shallow embayment, Ago Bay, of central Japan, where light penetrated to the seafloor. The in situ emergence flux (cells m-2 day-1) was measured by experiments using a ‘plankton emergence trap/chamber (PET chamber)’. During the study period from July 2006 to May 2008, germinating and rejuvenating cells of centric diatoms were successfully collected by the PET chamber. Furthermore, vegetative cells forming long-chain colonies, including the species which have not been known to form resting stage cells, were also found, indicating that these cells already inhabited the surface sediment prior to the start of the PET chamber experiments. The vegetative cells could be cells that grew after germination/rejuvenation and/or cells deposited from the upper layer in the water column. When comparing emergence flux in the PET chamber and the integrated abundance of the vegetative cells in the water column for the diatoms frequently observed, significant positive relationships were found for some diatom taxa. However, even for these taxa that showed a clear relationship, the magnitude of the vegetative population in the water column did not necessarily correlate with that of the emergence flux. These observations indicate that the magnitude of the vegetative population was not regulated directly by the emergence flux. The magnitude of the vegetative population could be dependent on the vegetative growth itself. This implies that the presence of vegetative cells in the water column is important at the time when environmental conditions become suitable for vegetative growth. In this context, the presence of various types of cells, such as germinating, rejuvenating, and vegetative cells, in the sediment is essential as seeds waiting for recruitment into the water column. Consequently, the seafloor in Ago Bay may act as a ‘refuge and nursery’ for centric diatoms. Based on the above, we demonstrated various patterns of life cycle strategies of the diatoms in a shallow coastal water/embayment.